2017
DOI: 10.1007/s13577-017-0167-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stim1 expression is associated with acquired chemo-resistance of cisplatin in osteosarcoma cells

Abstract: Osteosarcoma is the most common primary malignant bone tumor. Although cisplatin is the primary chemotherapy used in osteosarcoma treatment, the cisplatin resistance remains a big challenge for improving overall survival. The store-operated calcium (Ca2+) entry (SOCE) and its major mediator Stim1 have been shown to be implicated in a number of pathological processes typical for cancer. In this study, we showed that Stim1 expression was significantly increased in chemo-resistant osteosarcoma tissues compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…To accomplish this, both the parental and the CisR OC cells were treated with 50 µM of cisplatin for 24 h. Our results revealed that CisR cells had a poor apoptotic signature profile with a reduced level of apoptotic proteins (Bax, cleaved caspase-9 and cleaved caspase-3) and an increased level of anti-apoptotic protein (Bcl-2) compared to parental OC cells ( Figure 5 C,D) [ 50 ]. Subsequently, cisplatin significantly increased the expression of molecular markers of ER stress, such as GRP78, CHOP in parental OC cells compared to CisR OC cells [ 51 , 52 ]. Taken together, these findings demonstrate that cisplatin-induced ER stress-mediated apoptosis was significantly diminished in the CisR cells compared to the parental OC cells, which may point to an important underlying mechanism of CisR OC to avoid cellular death by cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish this, both the parental and the CisR OC cells were treated with 50 µM of cisplatin for 24 h. Our results revealed that CisR cells had a poor apoptotic signature profile with a reduced level of apoptotic proteins (Bax, cleaved caspase-9 and cleaved caspase-3) and an increased level of anti-apoptotic protein (Bcl-2) compared to parental OC cells ( Figure 5 C,D) [ 50 ]. Subsequently, cisplatin significantly increased the expression of molecular markers of ER stress, such as GRP78, CHOP in parental OC cells compared to CisR OC cells [ 51 , 52 ]. Taken together, these findings demonstrate that cisplatin-induced ER stress-mediated apoptosis was significantly diminished in the CisR cells compared to the parental OC cells, which may point to an important underlying mechanism of CisR OC to avoid cellular death by cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…OS has high morbidity and mortality. Moreover, the use of chemotherapy (cisplatin; Chen, 2017 ; Sun et al, 2017 ), doxorubicin (Hattinger et al, 2017 ; Zhang et al, 2017 ), and methotrexate (Valle et al, 2016 ; Ray et al, 2017 ) results in marginal improvement in survival rate even after surgery. The most serious problem is that survival rates have changed little over the past decades because no new drug is available.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common, malignant primary bone tumor in children and adolescents ( Kansara et al, 2014 ; Valery et al, 2015 ; Gianferante et al, 2017 ). Over the last 20 years, cisplatin has been commonly used as an anticancer drug to treat osteosarcoma ( Jaffe, 2014 ; Isakoff et al, 2015 ; Sun et al, 2017 ). However, there has been no improvement in the survival of patients with drug-resistant osteosarcoma ( Lin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%